Why I Teach Advertising: Critical Voices. (May 2020) - Champlin, Sara
In this invited essay, I reflect on my enthusiasm for teaching as an early career professor. I would like to thank the Association for Education in Journalism and Mass Communication's (AEJMC) Advertising Division for selecting me as the 2019 Early Career Teaching Excellence in Advertising award recipient.